Melatonin provides protection against heat stroke‐induced myocardial injury in male rats. (27th February 2018) - Lin, Xiaojing; Zhao, Tingbao; Lin, Cheng‐Hsien; Zuo, Dan; Ye, Zhujun; Lin, Shide; Wen, Shaonan; Liu, Lin; Lin, Mao‐Tsun; Chang, Ching‐Ping; Chao, Chien‐Ming
Abstract: Objectives: This study aimed to investigate the cardioprotective effects of melatonin on heat stroke (HS) induced acute myocardial infarction in rats and to explore the underlying mechanisms. Methods: Myocardial injury was induced by subjecting the anaesthetized rats to a high ambient temperature of 43°C for 70 min. Such a high ambient temperature caused hyperthermia, hypotension and myocardial injury in rats. Rats were treated with melatonin (3 mg/kg) intravenously one hour before and followed by an additional dose immediately after heat stress. Key findings: At the onset of HS, animals displayed myocardial injury evidenced by increased levels of cardiac damage indicators (e.g. total lactate dehydrogenase, cardiac troponin I and creatine kinase‐MB), increased cardiac damage scores and suppressed left ventricular performance. Animals with HS also had increased cardiac oxidative stress evidenced by increased levels of lipid peroxidation (e.g. increased thiobarbituric acid reactive substances) and decreased levels of antioxidant enzymes (e.g. superoxide dismutase, catalase and reduced glutathione) and activated inflammation (e.g. increased levels of interleukin‐6 and tumour necrosis factor‐α). Pretreatment with melatonin significantly reversed the HS‐induced myocardial injury, cardiac oxidative stress and cardiac inflammation. Conclusions: Melatonin may protect against HS‐induced myocardial injury in male rats by mitigating oxidative stress and inflammation.